ANALISA PERILAKU RUMAH TANGGA DALAM MENGOLAH SAMPAH SEBAGAI UPAYA MENDUKUNG ENERGI ALTERNATIF REFUSE DERIVED FUEL (RDF) - Kuntum Khoiro Ummatin; Novantio Bagas Putra Pratama (Jurnal Ilmiah Dinamika Teknik, 2021)
Garbage is a problem in various cities in Indonesia. One of the waste processing is converting the waste into RDF (Refused Derived Fuel) which can be used as an alternative fuel to replace coal in the cement industry, because it has a high calorific value. In an effort to support waste management into RDF, it is necessary to improve starting from the waste sorting system starting from the household level. This study aims to identify and analyze several factors that influence household behavior in processing waste in Tuban Regency. This area was chosen as the object of research because there are 2 large cement industries that can use RDF as fuel. The survey was conducted on 110 respondents, and the results obtained with multiple linear regression tests, the largest coefficient value is the waste processing facility variable at 0.232, followed by the waste management knowledge variable at 0.197, the household awareness variable in supporting waste management at 0.082, and the government role variable at 0.082. 0.221